Campur Kode Komunikasi Jual Beli dalam Grup WhatsApp E-Commerce Perguruan Tinggi - Ritonga, Nur'ainun; Hakim, Rani Ismil; Jannah, Rauzatul; Daulay, Irmasani (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
The purpose of this research is to determine the forms of code mixing and the factors causing it in the Whatsapp group of E-Commerce Campus, the family of lecturers, and the academic community of STAIN Mandailing Natal. The research method used is descriptive qualitative. The primary data collection technique involves documentation, which entails collecting chat messages in the Whatsapp group for 24 days, from March 6, 2024, to March 29, 2024. Meanwhile, secondary data consists of books and scholarly articles related to the research title. The data analysis technique utilizes Milles and Huberman's theory, which includes data reduction, data display, and conclusion drawing/verification. The research results reveal the forms of code mixing in the Whatsapp group of E-Commerce Campus, comprising 28 word forms and 28 phrase forms. The factors causing code mixing are multilingual ability, educational background, diverse regional backgrounds, and the tendency to follow trends in buying and selling, often using English terms such as "ready," "order," and others.